Artificial Immune System Based Data Miner - Hassan Babiker, Amir Samir (2011)
The goal of this project is to show how to solve data mining classification problems using Clonal Selection Algorithm (CLONALG). A comparisons has been proposed between the CLONALG and other classification techniques to show the performance and the accuracy of it.